2011
DOI: 10.1016/j.jtcvs.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyperglycemia on perioperative mortality after coronary artery bypass graft surgery

Abstract: Postoperative hyperglycemia is associated with increased in-hospital mortality in nondiabetic patients after coronary artery bypass graft surgery. In diabetic patients, hyperglycemia was not associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…The current study reported the same outcome, that the use of dexmedetomidine decreases the risk of hyperglycemia after cardiac surgery. Since postoperative hyperglycemia is associated with increased in-hospital mortality in non-diabetic patients after cardiac surgery [33,34], this property may help the clinicians to better control plasma glucose levels after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The current study reported the same outcome, that the use of dexmedetomidine decreases the risk of hyperglycemia after cardiac surgery. Since postoperative hyperglycemia is associated with increased in-hospital mortality in non-diabetic patients after cardiac surgery [33,34], this property may help the clinicians to better control plasma glucose levels after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may exhibit abnormal glucose levels only in the perioperative period. Previous studies have shown that nondiabetic patients with glucose levels >250 mg/dL who did not receive insulin therapy have increased hospital mortality [50]. Hence, as is discussed below, it is important that all cardiac surgical patients with elevated perioperative glucose values be treated with continuos insulin infusions, irregardless of whether a preoperative diagnosis of diabetes has or has not been established.…”
Section: The Role Of Tight Glycemic Control In Nondiabetic Cabg Pamentioning
confidence: 99%
“…Hyperglycemia affects the clinical outcomes after cardiac surgery. [ 3 4 5 6 7 8 9 10 11 12 13 ] Therefore, it is desirable to control hyperglycemia to improve prognosis. However, the risk of hypoglycemia becomes a limiting factor.…”
Section: Introductionmentioning
confidence: 99%